On Terms of Foreign Borrowing - Bardhan, Pranab (American Economic Review, 1973)
The theoretical literature on terms of foreign borrowing is rather narrow in the range of issues analyzed. Much of the recent literature is on an elaboration of the standard tariff argument to the case where services of capital are internationally purchased.' It is now well-known that a borrowing country, if it is an important borrower in the international capital market, may gain by restricting its international borrowing; depending on the relevant elasticities, one can easily work out the optimum terms (or the interest rate) at which borrowing should be done so that the monopoly power (strictly, monopsony power in the purchase of capital services) in the international capital market is fully utilized. For many borrowing countries, particularly in the underdeveloped world, the relevance of this analysis is, however, limited. These countries, taken individually, are often small borrowers in the international capital market and the task of setting on the national level the optimum terms of borrowing on the basis of their monopsony or oligopsony power is not particularly relevant. But a more significant limitation is that the whole analysis is static and ignores important time dimensions involved in problems of capital borrowing. The present paper concentrates on one such dimension. The terms of a foreign loan involve not merely the interest rate but also a maturity period by which time the loan is to be paid back. In the real world a borrowing country is often confronted with a choice among alternative loan packages with varying rates of interest and lengths -of maturity period. From the point of view of the long-run benefits of the borrowing country, how should one choose between a loan with, say, 5 percent rate of interest and a maturity period of 20 years and another loan with a higher, say, 7 percent rate of interest but a longer maturity period of, say, 30 years? Or, to put it in other words, in the long run is a rise in the interest rate on the foreign loan by a certain percentage costlier than a given shortening of the maturity period? This is an important practical problem in loan negotiations, and the existing theoretical literature on foreign borrowing does not throw much light on it.2 The present paper tries to answer the problem in terms of a verv simple dynamic model. I take a Harrod-Domar growth model with its drastically simplifying assumptions of a constant capital-output ratio and the ratio of savings to national income. There is only one commodity, and problems of trade with incomplete specialization are ignored. The for ign loan under consideration is a oncefor-all addition to the capital stock of the country. For simplification again, all capital is assumed to last forever, but the foreign loan has to be amortized in equal annual installments. I also ignore the gestation lag between availability of capital and its yield of output. National income, Y, is given by